2022
DOI: 10.1002/ams2.731
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the coronavirus disease 2019 (COVID‐19) pandemic on the incidence of heat stroke and heat exhaustion in Japan: a nationwide observational study based on the HeatstrokeSTUDY2019 (withoutCOVID‐19) and 2020 (withCOVID‐19)

Abstract: Aim To assess heat stroke and heat exhaustion occurrence and response during the coronavirus disease 2019 pandemic in Japan. Methods This retrospective, multicenter, registry‐based study describes and compares the characteristics of patients between the months of July and September in 2019 and 2020. Factors affecting heat stroke and heat exhaustion were statistically analyzed. Cramér’s V was calculated to determine the effect size for group comparisons. We also investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…The early risk assessment tool for detecting clinical outcomes in patients with heat-related illness, called the J-ERATO score, was defined as the sum of six binary components in the prehospital setting (respiratory rate ≥ 22 /min, Glasgow Coma Scale score < 15, systolic blood pressure ≤ 100 mmHg, heart rate ≥ 100 bpm, body temperature ≥ 38 °C, and age ≥ 65 years), with a total score ranging from 0 to 6 (Supplemental Table 1 ). We demonstrated that the J-ERATO score is accurate in predicting ICU admission and in-hospital mortality 11 , 12 . Furthermore, the usefulness of the J-ERATO score has been successfully validated in South India, which has a population with a different age distribution to Japan 13 .…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…The early risk assessment tool for detecting clinical outcomes in patients with heat-related illness, called the J-ERATO score, was defined as the sum of six binary components in the prehospital setting (respiratory rate ≥ 22 /min, Glasgow Coma Scale score < 15, systolic blood pressure ≤ 100 mmHg, heart rate ≥ 100 bpm, body temperature ≥ 38 °C, and age ≥ 65 years), with a total score ranging from 0 to 6 (Supplemental Table 1 ). We demonstrated that the J-ERATO score is accurate in predicting ICU admission and in-hospital mortality 11 , 12 . Furthermore, the usefulness of the J-ERATO score has been successfully validated in South India, which has a population with a different age distribution to Japan 13 .…”
Section: Introductionmentioning
confidence: 84%
“…Since 2017, this registry has been used to gather information regarding only patients admitted to the hospital owing to a diagnosis of heat-related illness. Approximately 142 emergency hospitals from all over Japan took part in the registry during the study period 12 . Data were manually recorded by the staff at each participating hospital by using standardized record sheets.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we performed retrospective analyses of data from the JAAM heatstroke registry, a nationwide multicenter observational registry collated annually since 2014 by the JAAM 11 . In 2019 (1 July–30 September), 148 hospitals participated in data collection (see acknowledgements).…”
Section: Methodsmentioning
confidence: 99%
“…According to the Japanese Association for Acute Medicine Heatstroke STUDY, 62.6% of the cases in 2019 were treated with extracellular fluid infusion without active cooling, whereas 70.0% of the cases in 2020 were treated in this manner. Furthermore, the percentage of active cooling methods that used evaporative plus convective cooling was 77.9% in 2019, but this decreased to 61.6% in 2020 54 .…”
Section: Literature Collection and Review Processmentioning
confidence: 99%